Thyroid hormones derivatives reduce proliferation and induce cell death and DNA damage in ovarian cancer. Issue 1 (December 2017) - Shinderman-Maman, Elena; Cohen, Keren; Moskovich, Dotan; Hercbergs, Aleck; Werner, Haim; Davis, Paul; Ellis, Martin; Ashur-Fabian, Osnat
Abstract Ovarian cancer is a highly aggressive disease and novel treatments are required. Thyroid hormones binding to αvβ3 integrin produced growth-promoting activities in ovarian cancer and we hypothesized that natural thyroid hormone derivatives may antagonize these actions. The effect of three antagonists, tetraiodoacetic acid (tetrac), triiodothyroacetic acid (triac) and 3-iodothyronamine (T1AM), on cell proliferation, cell death and DNA damage was studied in two ovarian cancer cell lines (OVCAR3 and A2780), normal hamster ovary control cells (CHOK1) and αvβ3-deficient or transfected HEK293 cells. A differential inhibition of cell proliferation was observed in ovarian cancer cells compared to CHOK1. In OVCAR3, an induction of cell cycle regulators was further shown. Apoptosis was confirmed (annexin-PI, SubG1/cell-cycle, apoptotic genes, caspase-3 and poly ADP ribose polymerase-1 (PARP-1) cleavage) and was reversed by a pan-caspase inhibitor. Induction in apoptosis inducing factor (AIF) was observed, suggesting a parallel caspase-independent mechanism. Integrin-involvement in triac/T1AM apoptotic action was shown in αvβ3-transfected HEK293 cells. Lastly, in ovarian cancer models, key proteins that coordinate recognition of DNA damage, ataxia-telangiectasia mutated (ATM) and PARP-1, were induced. To conclude, the cytotoxic potential of thyroid hormone derivatives, tetrac, triac and T1AM, in ovarian cancer may provide a much-needed novel therapeutic approach.